Unexpected serious aplastic anemia from PD-1 inhibitors: beyond what we know. Issue 6 (December 2019) - Filetti, Marco; Giusti, Raffaele; Di Napoli, Arianna; Iacono, Daniela; Marchetti, Paolo
Introduction: The recent introduction of checkpoint inhibitor–based immunotherapy has revolutionized the treatment of advanced lung cancers, becoming standard of care in both first- and second-line treatment. New types of toxicity are emerging with the increasingly widespread use of these inhibitors. Case presentation: We describe a case of aplastic anemia in a patient with stage IV non-small cell lung cancer after a single administration of nivolumab. Conclusions: Several similar case reports reported in literature show an increasing rate of toxicities from immunotherapy in this setting. These real-world data provide an insight into patient outcomes and treatment decisions being made in clinical practice.